Lucanus qizhihaoi, a new stag beetle from Wuyishan National Park of Fujian, China (Coleoptera: Lucanidae: Lucaninae) - Lin, Xin; Su, Rong-Xiang; Xin, Fei-Yi; Liao, Zhi-Yu; Lu, Huang-Hui; Liu, Xian-Zhou; Song, Hai-Tian (Zootaxa, 2024)
A new stag beetle species is described from Wuyishan National Park of Fujian, China, Lucanus qizhihaoi Lin, Su, Xin & Song, new species, which represents the easternmost distribution record of the L. boileaui group, previously known only from southwestern China and northern Indochina Peninsula. Evidences are found on morphological characters, the mitochondrial marker COI and significant geographic isolation to clearly distinguished the new species from its closest relative, L. boileaui Planet, 1897.